Diagnosis of progressive disseminated histoplasmosis in advanced HIV: A meta-analysis of assay analytical performance (2019)
Histoplasmosis is an important cause of mortality in people with advanced HIV, especially in countries with limited access to diagnostic assays. Histoplasmosis can be diagnosed using culture, histopathology, and antibody, antigen, and molecular assays. Several factors may affect the analytical performance of these laboratory assays, including sample type, clinical stage of the disease, and previous use of antifungal treatment, among others. Here we describe the results of a systematic literature review, followed by ameta-analysis of the analytical performances of the diagnostic laboratory assays employed. Our initial search identified 1631 references, of which 1559 references were excluded after title and abstract screening, leaving 72 references identified as studies relevant to the validation of histoplasmosis diagnostic assays. After evaluating the full text, 30 studies were selected for final review, including one paper not identified in the initial search. The meta-analysis for assay analytical performance shows the following results for the overall sensitivity (Sen) and specificity (Spe) of the various methods evaluated: Culture, Sen 77%(no data for specificity calculation); antibody detection assays, Sen 58%/Spe 100%; antigen detection assays, Sen 95%/Spe 97%; and DNA detection assays (molecular), Sen 95%/Spe 99%. Of the 30 studies reviewed, nearly half (n = 13) evaluated Histoplasma antigen assays, which were determined to be the most accurate methodology for diagnosis of progressive disseminated histoplasmosis in advanced HIV (inverse of the negative likelihood ratio was 13.2). Molecular assays appear promising for accurate diagnosis of histoplasmosis, but consensus on exact techniques is needed. Cultures showed variable sensitivity related to sample type and laboratory handling. Finally, antibody assays presented high specificity but low sensitivity. This poor sensitivity is most likely due the highly immunosuppressed state of this patient population. Diagnostic assays are crucial for accurate diagnosis of progressive disseminated histoplasmosis (PDH) with advanced HIV disease. © 2019 by the authors. All rights reserved.